(untitled) (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze iron deficiency anemia in children aged 0 to 5 years. Literature Review: Anemia is defined by the World Health Organization (WHO) as a condition in which the hemoglobin content in the blood is below normal as a result of a lack of one or more essential nutrients, whatever the cause, with iron deficiency being the most common. Iron deficiency in children is among the most prevalent food deficiencies in the world, being an alarming situation for public health, also known to be the cause of iron deficiency anemia (FA). The deficiency of these micronutrients causes a deficit in child growth and development. Iron’s main functions in the body are the transport of oxygen to the cells, in addition to participating in the enzymatic systems of various tissues. Final considerations: It is noteworthy that the high causal potential of iron deficiency anemia in the population, especially in the child population, can thus compromise child development markedly and inhumanely. In addition, it is seen that numerous ways of prevention, control and treatment are necessary to prevent children from suffering from these conditions.